ЗЕРТХАНАЛЫҚ ЖАНУАРЛАРДЫҢ ЖОҒАРҒЫ АСҚОРЫТУ ЖҮЙЕСІНІҢ АНАТОМИЯСЫН САЛЫСТЫРМАЛЫ ТАЛДАУ - А. Джангабулова; Д. Калкаева; Б. Турумбетов; Г. Омарбекова; С. Нусупова; А. Мыржиева; Н. Нурходжаев; С. Ахметова; А. Өсербай; Г. Мухпулова (Animal Health and Biosafety, 2026)
This study is aimed at a comparative anatomical analysis of the structural features of the upper digestive system of laboratory animals. The objective of the work is to identify morphological differences in the upper digestive organs among various laboratory animal species (such as rodents and lagomorphs) and to quantitatively assess them using digital reconstruction methods. During the study, high-resolution imaging technologies (micro-computed tomography and digital modeling) were employed to generate three-dimensional models of the esophagus, the proximal part of the stomach, and adjacent structures. Morphometric parameters (volume, surface area, length, and spatial configuration) were measured using specialized software. The results revealed distinct morphological and functional adaptations of the upper digestive system among the studied animals. In particular, anatomical differences related to feeding type were identified, which represent an important factor influencing the efficiency of digestive processes. In addition, shown to provide more accurate and visually informative characterization of structures compared to traditional morphological analysis. In conclusion, this study contributes to a deeper understanding of the digestive system of laboratory animals and provides a scientific basis for the selection of experimental models. The findings are significant for further research in veterinary science, biomedicine, and comparative anatomy.